Bariatric Surgery Outcomes in the Elderly: An ACS NSQIP Study - Dorman, Robert B.; Abraham, Anasooya A.; Al-Refaie, Waddah B.; Parsons, Helen M.; Ikramuddin, Sayeed; Habermann, Elizabeth B. (Journal of gastrointestinal surgery, 2012)
Introduction Mortality and complications following bariatric surgery occur at acceptable rates, but its safety in the elderly population is unknown. We hypothesized that short-term operative outcomes in bariatric surgery patients ≥65 years would be comparable to younger persons. Methods Patients with a body mass index ≥35 kg/m 2 who underwent bariatric surgery in the 2005–2009 American College of Surgeons National Surgical Quality Improvement Program were identified. Controlling for confounders, multivariate regression was used to predict the impact of age on mortality, major events and prolonged length of stay at 30 days. Results We identified 48,378 patients who underwent bariatric procedures between 2005 and 2009. Multivariate regression analysis demonstrated advancing age trended towards predicting mortality, but was not statistically significant. Additionally, patients ≥65 years did not experience higher risk of major complications for either open or laparoscopic procedures. However, patients age ≥65 years were more likely to experience prolonged length of stay for both open and laparoscopic procedures. Conclusion This multi-hospital study demonstrates older age predicts short-term prolonged length of stay but not major events following bariatric surgery. Older age trends toward predicting mortality, but it is not statistically significant.